Establishing an Institute of Speech-Language Therapy in Pakistan - Amina Asif Siddiqui (ziauddin University, 2024)
We communicate all the time, everywhere and witheveryone through what we speak, read, write andunderstand others. Our gestures, facial expressions,body language and the tone of our voice add to the messages that are exchanged hetween us. Information technology has revolutionized the exchange of information amongst us. A ship captain in mid ocean can talk to personnel ashore via telephone; the Global Positioning System informs us of our place on earth anywhere and everywhere, we skype, send text messageswith written words, symbols and pictures, and use sign language. The world has indeed become a global village, very different from the village where a drummer would beat the drum in the lanes to inform the people of the King's proclamation! Key Words: Pregnant Females, Antenatal Care, Physical Therapy.